Regional differences in overweight: an effect of people or place?. Issue 5 (18th December 2007) - Hawkins, S S; Griffiths, L J; Cole, T J; Dezateux, C; Law, C; ,
Abstract : Objective: To examine UK country and English regional differences in childhood overweight (including obesity) at 3 years and determine whether any differences persist after adjustment for individual risk factors. Design: Nationally representative prospective study. Setting: England, Wales, Scotland and Northern Ireland. Participants: 13 194 singleton children from the UK Millennium Cohort Study with height and weight data at age 3 years. Main outcome measure: Overweight (including obesity) was defined according to the International Obesity TaskForce cut-offs for body mass index, which are age and sex specific. Results: At 3 years of age, 23% (3102) of children were overweight or obese. In univariable analyses, children from Northern Ireland (odds ratio 1.30, 95% confidence interval 1.14 to 1.48) and Wales (1.26, 1.11 to 1.44) were more likely to be overweight than children from England. There were no differences in overweight between children from Scotland and England. Within England, children from the East (0.71, 0.57 to 0.88) and South East regions (0.82, 0.68 to 0.99) were less likely to be overweight than children from London. There were no differences in overweight between children from other English regions and children from London. These differences were maintained after adjustment for individual socio-demographic characteristics and other risk factors for overweight. Conclusions: UK country and English regional differences in early childhood overweight are independent of individual risk factors. This suggests a role for policies to support environmental changes that remove barriers to physical activity or healthy eating in young children.